SISTEM PELAYANAN JASA SERVIS MOTOR BERBASIS SMS GATEWAY DENGAN MENERAPKAN METODE CRM (STUDI KASUS BENGKEL AHASS AS PUTRA MOTOR) - Rudi Lesmana (FKOM UNIKU, 2017)
AHASS AS Putra Motor is a workshop that provides motorcycle vehicle service for Honda brand. In addition, it also provides a variety of vehicle parts and accessories. All the service and spare parts processes conform to the standard of service set by Honda. In an effort to improve services to its customers AHASS AS Putra Motor seeks to provide convenience for customers to make booking services online. It makes easy for customers to schedule their vehicle service in the midst of busy customers. The system built is a system of information booking service service in AHASS AS Putra Motor with SMS Gateway based. This Web-based booking system is built by using Rational Unified Process (RUP) software development methodology by implementing CRM (Customer Relationship Management) method as one of the means to establish good relationships with customers and simplify the services provided. It is built using PHP and CI, and MySQL as data storage.To test the system uses black box white box testing.This system is expected to be a solution to overcome the existing problems and it can improve the service provided by AHASS AS Putra Motor